Brand Trust as Mediator Between Influencer Marketing, Brand Image, and Repurchase Intention at Rabbani - Lestari, Yuliantika Dwi; Kurniawan, Ryan (Journal of Applied Business, Taxation and Economics Research, 2025)
This research explores how consumers perceive influencer marketing, brand image, brand trust, and their intention to repurchase. It also investigates the role of influencer marketing and brand image in shaping repurchase behavior, with brand trust serving as a mediating factor. A quantitative approach was used, involving 100 participants who had previously purchased Rabbani products and were active social media users. The results reveal that both influencer marketing and brand image significantly influence repurchase intentions, both directly and indirectly through brand trust. Influencer marketing enhances brand trust through the perceived credibility, appeal, and expertise of the influencers selected by Rabbani. Similarly, brand image plays a key role in boosting trust by shaping positive consumer perceptions of product quality and the brand’s overall reputation. Brand trust itself contributes positively to the likelihood of repurchasing; consumers with higher levels of trust in Rabbani are more inclined to buy again. In conclusion, brand trust acts as a crucial mediator that reinforces the impact of influencer marketing and brand image on consumers’ repurchase intentions.